2022
DOI: 10.1371/journal.pone.0266950
|View full text |Cite
|
Sign up to set email alerts
|

Association between self-care disability and depressive symptoms among middle-aged and elderly Chinese people

Abstract: Objective In the context of an increased focus on geriatric depression in recent years, this study examined the associations between different types of self-care disability, the number of self-care disabilities, and depressive symptoms among middle-aged and elderly Chinese people. Method The data for this study were extracted from the follow-up survey (conducted in 2018) of the China Health and Retirement Longitudinal Study (CHARLS). The sample comprised 10808 participants aged 45 years and older. The Activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 42 publications
(50 reference statements)
0
16
1
Order By: Relevance
“…Therefore, the years of schooling were divided into 0 years (illiterate), 1 to 9 years (elementary school or middle school), and over 10 years (high school and above), according to the length of different learning stages. Previous studies found that individuals with higher levels of education have a lower risk of depressive symptoms ( 28 , 29 ).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, the years of schooling were divided into 0 years (illiterate), 1 to 9 years (elementary school or middle school), and over 10 years (high school and above), according to the length of different learning stages. Previous studies found that individuals with higher levels of education have a lower risk of depressive symptoms ( 28 , 29 ).…”
Section: Methodsmentioning
confidence: 97%
“…In all individuals with a disability, difficulty completing 1–2 activities, 3–4 activities, and 5–6 activities were considered mild, moderate, and severe disability, respectively. Our previous study found that individuals with higher levels of disability were at greater risk of depressive symptoms ( 29 ). The Cronbach's αvalue was 0.908, indicating a reasonable reliability level.…”
Section: Methodsmentioning
confidence: 99%
“…[17] A study found a positive correlation between the number of self-care disorders and the risk of depressive symptoms. [18] Another study found that regular and appropriate outdoor activities among elderly people can reduce the risk of depression. [19] However, the amount of research evidence on the impact of walking ability and self-assessment of health on depression is limited, and the scientific quality of various studies varies.…”
Section: Introductionmentioning
confidence: 99%
“…[17] A study found a positive correlation between the number of self-care disorders and the risk of depressive symptoms. [18] Another study found that regular and appropriate outdoor…”
Section: Introductionmentioning
confidence: 99%
“…People with disabilities can be at a greater risk for falling, hospitalization and death 1 . It is estimated that more than 20% of middle‐aged and older adults (i.e., ≥45 years old) have disabilities in 2018 2 . The greater risk of disability among middle‐aged and older adults is potentially because many middle‐aged and older adults have multiple co‐occurring age‐related disorders, such as the declined cognitive and physical functions.…”
Section: Introductionmentioning
confidence: 99%